Engineering Education and Engineering Practice: A Student Teacher Perspective - Kantonidou, M. M. (Elektronika ir Elektrotechnika, 2010)
The paper presents the results of a qualitative and quantitative study of electrical and electronic engineering student teacher perceptions of (a) engineering education, and (b) engineering practice. The study was conducted in ASPETE, the sole HE School for the education and training of prospective engineering educators in Greece. Data came from semi-structured interviews of selected informants across ASPETE’s Departments of Electrical and Electronic Engineering Educators, and a questionnaire survey of a stratified random sample. Given the relative scarcity of information on the issue, an understanding of such perceptions can provide useful insights for educators and curriculum developers.